The Impact of Overtime Limits on Firms and Workers: Evidence from Japan's Work Style Reform - Gabriel Burdin; Ryo Kambayashi; Takao Kato (Institute of Labor Economics (IZA), 2024)
This study provides the first analysis of Japan's 2018 Work Style Reform (WSR) and its effects on firms and workers, using payroll and survey data in a difference-in-difference design. We find that the reform's introduction of an overtime cap reduces average monthly overtime hours by 5 hours (-25%) and compresses the distribution of overtime within establishments. Total earnings decrease by 2% due to reduced overtime pay, while hourly wages remain unchanged. Notably, the reform improves life and leisure satisfaction, but these well-being gains are observed only among women. This gender difference is not explained by variations in perceived work intensification or time use. Instead, we find evidence that men (but not women) substitute paid overtime for unpaid overtime, which is consistent with the lack of well-being gains for men. Finally, we document that the reform leads to women taking more career jobs (standard employment) relative to non-career jobs (nonstandard employment) as compared to their male counterparts, highlighting the potential of working-hour regulations to promote gender equality in the labor market.
Keywords: J16; J22; J23; J41; 330; working time regulations; overtime; wages; employment; subjective well-being; gender; Japan; work style reform